STUDI PENERAPAN DESAIN UNIVERSAL PADA MASJID MANARUL AMAL KAMPUS MERUYA DI UNIVERSITAS MERCU BUANA JAKARTA BARAT - Randi Sanjaya; Rachmita Maun Harahap; Henny Gambiro (Universitas Mercu Buana, 2019)
Mosque design based on the universal design principle is a design concept for a mosque architecture that can be used by a person with disability users. Mosque as the center of religious activities is ‘Allah’s house’ where the congregation conducts praying. Shalat is essential to worship in Islam done at least five times a day and cannot be abandoned unless very specific condition happens (as explained in Al Qur’an). But in fact, hearing disability users still find difficulties in accessing mosques, most mosques are not accessible. This study aims to describe of study of universal design application at the Manarul Amal mosque on the Meruya campus at Mercu Buana University for a person with disabilities. The universal design principle is chosen based on the possibilities it provides to explore each potential tool to reduce or even eliminate the physical barrier for its users. This research method uses a qualitative descriptive method. The instrument of this study was researchers who were assisted with observation guidelines, interview guidelines and documentation guidelines based on the grid Minister of Public Works Regulation No. 14 / PRT / M / 2017. The steps of data analysis carried out include: data reduction, data presentation, and conclusion. The results showed that the interior elements in the Manarul Amal mosque were in form of circulation, guiding paths, ramps, prayer rooms, sermon rooms, ablution rooms, shelves for footwear (shoes and feet) and supporting facilities attributes that didn’t meet the standard. While the walls of a room aren’t equipped with handrail, lighting, and colors are sufficient to meet the standards and audiovisual that is around the prayer room without a TV text, visual alarm (sound calling when praying).